Intrinsic Institutional Advantages to the West: Economic Rise of China - Rai, Kamal (Molung Educational Frontier, 2026)
This research paper examines the high-profile formal international institutional advantages that the West has gained in the global order since the post-war era. Since the mid-1940s, nearly 90% of key international institutions have been founded and operate worldwide. Institutions underpin the global eco-political order because they are instrumental in structure and political in nature. Thus, the West remains structurally powerful enough to maintain its supremacy in the international order. However, global institutions are not permanent, as powerful countries often seek to establish such institutions in their favour. The historical shift reveals that institutional locations frequently change in tandem with the country’s shifting global hegemony. This article analyses the influence of global institutions and their roles in the 21st century, adopting institutionalism as the theoretical lens. Institutionalism in IR as a theoretical approach primarily focuses on the prominent roles of formal institutions as soft power actors in anarchical power politics and the global order. Since the 1980s, China has experienced remarkable economic growth and is expected to surpass the USA in the late 2020s, potentially relocating high-status institutions out of the West. Therefore, it may be extremely challenging for the West to maintain its global institutional dominance in the 21st century.